Spatial distribution of suspended solids during short-term high river discharge in the Bay of Koper, northern Adriatic Sea - SOCZKA MANDAC, ROK; ŽAGAR, DUŠAN (Mediterranean Marine Science, 2018)
The Bay of Koper (BoK) located in the Gulf of Trieste (northern Adriatic Sea) is subject to a variety of anthropogenic influences; pollutants from inland are transported to the sea by the local rivers. The impact of high river discharge on suspended solids distribution was assessed by analysing results of an extensive measurement campaign conducted during two episodes of river flooding. The spatial analysis demonstrated the area influenced by fresh water and the distribution of inorganic suspended solids (ISS). The results were then used to calibrate the PCFLOW3D model and to simulate two episodes. A correlation was identified between the measurements and short-term simulations found in the central part of the bay. The results confirm the methods and the model used in this study to be appropriate for studying complex suspended solids processes in coastal areas.